Redescriptions of two physonect siphonophores, Apolemia uvaria (Lesueur, 1815) and Tottonia contorta Margulis, with comments on a third species Ramosia vitiazi Stepanjants - Mapstone 2003, G. M. (Cnidaria: Hydrozoa: Apolemiidae). Systematics and Biodiversity, 1976)
Two species referable to the physonect siphonophore family Apolemiidae are re-described: Apolemia uvaria (Lesueur, 1815), the type species, and Tottonia contorta Margulis, 1976. Descriptions, based mainly on three colonies from the Mediterranean (A. uvaria) and three taken off California (T. contorta) contain new information on some zooids and update previous information on others. Figures show the arrangement of nectophores on the nectosomal stem, budding zones, possible degenerative zones and all zooid types (except gonophores in A. uvaria). The morphology of these two species is discussed in relation to a third species Ramosia vitiazi Stepanjants, 1967. These descriptions provide a benchmark for up to 10 putative new species of apolemiids believed to exist but not yet described.